Pengaruh Live Streaming Dan Affiliate Marketing Terhadap Keputusan Pembelian Spontan Pada Tik Tok - Lalu Billy Maulana Sanjaya; Era Agustina Yamini (Jurnal Ekonomi dan Bisnis Digital, 2025)
The advancement of digital technology has transformed consumer behavior in making purchasing decisions, particularly through the Tik Tok platform, which offers live streaming features and affiliate marketing programs. This study aims to determine the impact of live streaming and affiliate marketing on spontaneous purchase decisions among Tik Tok users in the Special Region of Yogyakarta.This research employed a quantitative approach using a survey method with a questionnaire distributed to 210 respondents who have made spontaneous purchases through Tik Tok live. Data were analyzed using multiple linear regression tests with the assistance of SPSS software. The results indicated that affiliate marketing had a positive and significant effect on spontaneous purchase decisions, while live streaming did not have a significant effect. Simultaneously, both independent variables, namely live streaming and affiliate marketing, significantly influenced spontaneous purchase decisions with a significance value of 0.000 < 0.05. The coefficient of determination shows that 48.9% of the variation in spontaneous purchase decisions can be explained by these two variables, while the remaining percentage is influenced by other variables outside the scope of this study. These results imply that marketing strategies through affiliate marketing are more effective in driving spontaneous purchases compared to relying solely on live streaming features. This research is expected to serve as a reference for business practitioners and digital marketers in maximizing Tik Tok features as a strategic promotional tool.